Peculiarity of simulation of transitional processes on turbo fan engine with mixed flows - Панін, В. В.; Кінащук, І. Ф.; Купчик, М. В. (Proceedings of National Aviation University (archive), 2000)
Considered is a particular simulation of transitional process on turbo fan engine with mixed flows. The given models allow to define engine compressor working lines for uprated checking fitness according to parameter readings of airborne registration systems